Asymmetric structure coated diaphragm, preparation method and battery
By coating the separator with an asymmetric structure on the lithium battery separator, using the combination of high-temperature resistant aramid and PVDF, the existing separator has been solved, and the separator is adhered to positive and negative electrodes. Different junction forces and high heat resistance improve the safety and service life of lithium batteries.
Patent Information
- Application Number
- CN202411280826.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-13
AI Technical Summary
The slurry of the existing lithium battery separator has poor compatibility with the slurry, which makes the slurry easy to fall off, reducing the heat resistance of the slurry and the service life of the lithium battery. At the same time, the existing technology cannot achieve different adhesion between the slurry and the positive and negative electrodes. .
Coating the membrane with an asymmetric structure, including the first coating (high temperature resistant aramid), the third coating (high temperature resistant aramid and oily PVDF) and the second coating (water-based PVDF) on both sides of the base film ), through two-stage solidification bath treatment and appropriate molecular weight selection, the separator has different adhesion forces and high heat resistance.
The adhesive force between the diaphragm and the positive and negative electrodes is achieved, the heat resistance and battery safety performance of the diaphragm are improved, the service life of the battery is extended, and the production cost is reduced.
Smart Images

Figure CN118801048B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an asymmetric structure coated diaphragm, a preparation method and a battery, and belongs to the technical field of lithium battery materials. Background Art
[0002] In the structure of lithium batteries, the diaphragm is one of the key internal components. The diaphragm is located between the positive electrode and the negative electrode. Its main function is to separate the positive and negative active materials to prevent the two electrodes from short-circuiting due to contact, while allowing the rapid transport of charged ions. In order to improve the heat resistance of the diaphragm, a layer of slurry needs to be applied to the diaphragm to improve the safety performance of lithium batteries. However, at present, the compatibility between the slurry and the diaphragm in the relevant prior art is poor, which makes the slurry easy to fall off the diaphragm, resulting in a weakening of the heat resistance of the diaphragm product, which in turn affects the service life of the lithium battery.
[0003] With the development of battery technology, battery production efficiency has improved. On the basis of traditional winding and lamination processes, some battery companies have also developed more advanced thermal composite lamination processes. Usually, the lamination process or thermal composite lamination process requires a certain degree of adhesion between the diaphragm and the positive and negative electrodes to reduce the gap between the diaphragm and the positive and negative electrodes during the battery charging and discharging process, and improve the battery charging and discharging performance. The method currently used by diaphragm companies is to coat PVDF on the base film. For example: Chinese patent application CN105552284A discloses a composite coated lithium-ion battery diaphragm and a preparation method thereof, wherein a PVDF coating is coated on the battery diaphragm, and the PVDF coating used is obtained by coating and drying an aqueous PVDF slurry. In addition, Chinese patent application CN104993089A discloses an aramid-coated lithium-ion battery diaphragm and a preparation method thereof, wherein the diaphragm is composed of a lithium-ion battery base film and a coating on one or both sides of the base film, wherein the coating is obtained by coating, soaking, and drying an aramid slurry, and the aramid slurry is composed of an aramid fiber dissolving liquid, an emulsifier solution, and a polymer adhesive. Although these related technologies can effectively improve the adhesion between the diaphragm and the electrode piece, they cannot achieve different adhesion between the diaphragm and the positive and negative electrodes. For the positive and negative electrode materials and battery processes of the battery, there are differences in the adhesion between the positive and negative electrodes and the diaphragm, so it is necessary to achieve different adhesion between the positive and negative electrodes on both sides of the diaphragm, and for different electrode materials, the adhesion performance requirements for the diaphragm are different.
[0004] At present, commercialized PVDF diaphragms are mainly PVDF coated on polyolefin diaphragms mainly composed of polyethylene and polypropylene, including water-based coating and oil-based coating. On the one hand, the bonding force between the positive and negative electrodes and the diaphragm is the same, and the bonding condition of the diaphragm cannot be regulated. On the other hand, there are safety hazards caused by poor heat resistance. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides an asymmetric structure coated diaphragm, a preparation method and a battery. The asymmetric diaphragm can not only meet the different bonding forces with the positive and negative electrodes, but also improve the heat resistance of the diaphragm, thereby improving the safety performance of the battery. At the same time, it can also meet the high bonding requirements, and the coating method is relatively simple, thereby reducing production costs.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: an asymmetric structure coated diaphragm, the asymmetric structure coated diaphragm comprises a base film, a first coating layer and a third coating layer are respectively provided on both sides of the base film, and a second coating layer is provided on the first coating layer;
[0007] The first coating is high temperature resistant aromatic polyamide; the third coating includes high temperature resistant aromatic polyamide and oily PVDF; and the second coating is water-based PVDF.
[0008] Furthermore, the high temperature resistant aromatic polyamide is meta-aramid, para-aramid, heterocyclic aramid or polyamide-imide;
[0009] The weight average molecular weight of the meta-aramid is 150,000-250,000; the weight average molecular weight of the para-aramid is 40,000-80,000; the weight average molecular weight of the heterocyclic aramid is 200,000-400,000; and the weight average molecular weight of the polyamide-imide is 100,000-300,000.
[0010] Furthermore, the weight average molecular weight of the oily PVDF is 400,000-800,000;
[0011] The difference in weight average molecular weight between the oily PVDF and the meta-aramid is not less than 250,000;
[0012] The difference in weight average molecular weight between the oily PVDF and the para-aramid is not less than 400,000;
[0013] The difference in weight average molecular weight between the oily PVDF and the heterocyclic aramid is not less than 250,000;
[0014] The difference in weight average molecular weight between the oily PVDF and the polyamide-imide is not less than 350,000.
[0015] Further, the first coating has a thickness of 0.5-4.0 μm, the third coating has a thickness of 0.5-4.0 μm, and the second coating has a thickness of 0.5-4.0 μm;
[0016] In the third coating, the mass ratio of high temperature resistant aromatic polyamide to oily PVDF is 1:(1-10); the hot pressing bonding force of the third coating is 1-30 N / m 2 The hot pressing bonding force of the second coating is 2-12 N / m 2 .
[0017] Furthermore, the air permeability of the asymmetric structure coated diaphragm is ≤300s / 100cc, and the membrane rupture temperature is ≥250°C.
[0018] The present invention also discloses a method for preparing an asymmetric structure coated diaphragm, the preparation method comprising:
[0019] S1, dispersing the high temperature resistant aromatic polyamide polymer solution in a polar solvent to obtain a casting solution A;
[0020] Mixing a high temperature resistant aromatic polyamide polymer solution and an oily PVDF in a polar solvent, and mixing them evenly to obtain a casting solution B;
[0021] S2, coating the casting liquid A and the casting liquid B on both sides of the base film to form a first coating layer and a third coating layer, and then performing a two-stage coagulation bath treatment, and finally washing and drying;
[0022] S3, coating the first coating with water-based PVDF slurry to obtain a second coating, drying and rolling up to obtain the asymmetric structure coated diaphragm.
[0023] Further, a pore-forming agent is added or not added to the casting liquid A and the casting liquid B, the mass content of the pore-forming agent in the casting liquid A is 0%-10%, and the mass content of the pore-forming agent in the casting liquid B is 0%-10%;
[0024] The porosity of the first coating layer is 30-70%, and the porosity of the third coating layer is 30-70%.
[0025] Furthermore, the coagulation bath is a mixed solution of a polar solvent and water, the mass concentration of the polar solvent in the first coagulation bath is 30%-45%, and the temperature of the first coagulation bath is 30-60°C; the mass concentration of the polar solvent in the second coagulation bath is 5%-15%, and the temperature of the second coagulation bath is 20-50°C.
[0026] Furthermore, the concentration difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥20%, and the temperature difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥10°C.
[0027] The invention also discloses a battery, wherein the battery contains the asymmetric structure coated diaphragm of the invention.
[0028] The beneficial effects of the present invention are:
[0029] The preparation method of the present invention can meet the different requirements of the bonding force between the diaphragm and the positive electrode and the negative electrode, better match the battery processing technology, and improve the battery cycle capacity retention rate. In addition, the asymmetric diaphragm preparation method of the present invention can specifically prepare a diaphragm with the required hot pressing bonding force. In actual production, a diaphragm that meets the requirements can be directly prepared according to the downstream application requirements, thereby greatly reducing the workload of exploring experimental conditions.
[0030] The preparation method of the present invention selects a high-temperature resistant aromatic polyamide polymer solution and PVDF of suitable molecular weight to prepare the diaphragm coating, and combines the setting of a two-stage coagulation bath to make the diaphragm have good heat resistance and good bonding performance. Because in the two-stage coagulation molding process, in the first-stage coagulation bath, the high-temperature resistant aromatic polyamide is first pre-solidified and formed, and PVDF is just filled in the surface pores of the pre-solidified high-temperature resistant aromatic polyamide; in the second-stage coagulation bath, PVDF and the unformed high-temperature resistant aromatic polyamide are completely solidified; this process can keep as much PVDF as possible on the surface of the diaphragm, so that the diaphragm can have good heat resistance and bonding performance at the same time. It can effectively solve the problem of poor adhesion of the diaphragm caused by the simultaneous molding of a mixed solution of a high-temperature resistant polymer and an adhesive polymer PVDF. At the same time, the setting of the coagulation bath conditions can make the diaphragm coating have good flatness and strength performance, and have uniform pores, and ultimately improve the comprehensive application performance of the diaphragm.
[0031] At present, the diaphragm production processes that can meet the requirements of heat resistance and adhesion of diaphragms on the market mostly prepare heat-resistant coatings first, and then apply secondary adhesive coatings after winding. In the preparation method of the present invention, double-sided coating can be applied simultaneously, which can meet the requirements of heat resistance and adhesion of diaphragms and reduce production costs.
[0032] The asymmetric structure coated diaphragm of the present invention can increase the diaphragm rupture temperature, improve the diaphragm heat resistance, and improve the battery safety performance. The asymmetric structure coated diaphragm has a permeability value of ≤300s / 100cc and a rupture temperature of ≥250°C, which can delay the battery heat spread time, reduce the thermal runaway temperature, and improve the battery safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a schematic diagram of the structure of the asymmetric structure coated diaphragm of the present invention;
[0034] Figure 2 This is a SEM image of the surface of the second coating layer of the asymmetric structure coated diaphragm in Example 1;
[0035] Figure 3 This is a SEM image of the surface of the third coating layer of the asymmetric structure coated diaphragm in Example 1. DETAILED DESCRIPTION
[0036] The specific implementation of the present invention is described in detail below. The present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed.
[0037] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and are not intended to limit the present invention.
[0038] An asymmetric structure coated diaphragm, the asymmetric structure coated diaphragm comprises a base film, two sides of the base film are respectively provided with a first coating and a third coating, the first coating is provided with a second coating, the specific structure is as follows Figure 1 As shown;
[0039] The first coating is high temperature resistant aromatic polyamide; the third coating includes high temperature resistant aromatic polyamide and oily PVDF; and the second coating is water-based PVDF.
[0040] Specifically, the high temperature resistant aromatic polyamide is meta-aramid, para-aramid, heterocyclic aramid or polyamide-imide;
[0041] The weight average molecular weight of the meta-aramid is 150,000-250,000; the weight average molecular weight of the para-aramid is 40,000-80,000; the weight average molecular weight of the heterocyclic aramid is 200,000-400,000; and the weight average molecular weight of the polyamide-imide is 100,000-300,000.
[0042] Specifically, the weight average molecular weight of the oily PVDF is 400,000-800,000;
[0043] The difference in weight average molecular weight between the oily PVDF and the meta-aramid is not less than 250,000;
[0044] The difference in weight average molecular weight between the oily PVDF and the para-aramid is not less than 400,000;
[0045] The difference in weight average molecular weight between the oily PVDF and the heterocyclic aramid is not less than 250,000;
[0046] The difference in weight average molecular weight between the oily PVDF and the polyamide-imide is not less than 350,000.
[0047] Specifically, the first coating has a thickness of 0.5-4.0 μm, the third coating has a thickness of 0.5-4.0 μm, and the second coating has a thickness of 0.5-4.0 μm;
[0048] In the third coating, the mass ratio of high temperature resistant aromatic polyamide to oily PVDF is 1:(1-10); the hot pressing bonding force of the third coating is 1-30 N / m 2The hot pressing bonding force of the second coating is 2-12 N / m 2 The hot-pressing bonding force of the third coating can be controlled by adjusting the ratio of the oily PVDF and the high-temperature resistant aromatic polyamide in the casting solution B.
[0049] Specifically, the air permeability of the asymmetric structure coated diaphragm is ≤300s / 100cc, and the membrane rupture temperature is ≥250°C.
[0050] A method for preparing an asymmetric structure coated diaphragm, the preparation method comprising:
[0051] S1, dispersing the high temperature resistant aromatic polyamide polymer solution in a polar solvent to obtain a casting solution A; the mass fraction of the high temperature resistant aromatic polyamide in the casting solution A is 2-10wt%;
[0052] Mixing a high temperature resistant aromatic polyamide polymer solution and an oily PVDF in a polar solvent, and mixing them evenly to obtain a casting solution B;
[0053] S2, coating the casting liquid A and the casting liquid B on both sides of the base film through a micro-concave roller to form a first coating and a third coating, and then performing a two-stage coagulation bath treatment, and finally washing with water for 30-300s and then drying in a drying oven at 40-80°C, and then rolling up after drying;
[0054] S3, coating the first coating with water-based PVDF slurry to obtain a second coating, drying at 40-80° C., and rolling up to obtain the asymmetric structure coated diaphragm. The coating method is spray coating or roller coating.
[0055] Specifically, a pore-forming agent is added or not added to the casting liquid A and the casting liquid B, the mass content of the pore-forming agent in the casting liquid A is 0%-10%, and the mass content of the pore-forming agent in the casting liquid B is 0%-10%;
[0056] The porosity of the first coating layer is 30-70%, and the porosity of the third coating layer is 30-70%.
[0057] More specifically, the pore-forming agent is PVP, PEG, etc., but is not limited to these. The pore-forming agent used in the embodiment of the present invention is PVP K30, PVP K90, PEG 200, PEG 400, PEG 800, PEG 1000 or PEG 2000.
[0058] More specifically, the water-based PVDF used in the embodiments of the present invention is LBG.
[0059] More specifically, the base film used in the embodiment of the present invention is a 7 μm PE film.
[0060] Specifically, the coagulation bath is a mixed solution of a polar solvent and water, the mass concentration of the polar solvent in the first coagulation bath is 30%-45%, and the temperature of the first coagulation bath is 30-60°C; the mass concentration of the polar solvent in the second coagulation bath is 5%-15%, and the temperature of the second coagulation bath is 20-50°C.
[0061] Specifically, the concentration difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥20%, and the temperature difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥10°C.
[0062] Specifically, the polar solvent is any one of N,N-dimethylacetamide, N,N-dimethylformamide, and N-methylpyrrolidone. The viscosity of the casting solution A and the casting solution B is 30-10000 mpa·s.
[0063] A battery comprises the asymmetric structure coated diaphragm of the present invention.
[0064] The following example is the preparation of an asymmetric structure coated separator, wherein the base film 1 used is a 7 μm PE film.
[0065] Example 1
[0066] (1) dissolving a meta-aramid polymer solution (weight average molecular weight of 200,000) in N,N-dimethylacetamide to obtain a casting solution A; the mass fraction of the meta-aramid in the casting solution A is 5 wt %, and the slurry viscosity of the casting solution A is 80 mpas;
[0067] The meta-aramid polymer solution (weight average molecular weight of 200,000) and oily PVDF (weight average molecular weight of 630,000) were mixed in N,N-dimethylacetamide at a certain solid content, and mechanically stirred for 0.5 h at 20°C to obtain a casting solution B after complete dissolution; in the casting solution B, the mass ratio of meta-aramid to PVDF was 1:5, and the slurry viscosity of the casting solution B was 95 mpas;
[0068] (2) The casting liquid A and the casting liquid B are simultaneously coated on both sides of the base film through a micro-concave roller to form a first coating layer and a third coating layer respectively, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40°C for 30 seconds after washing, and then rolled up after drying;
[0069] The first coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 40% and a temperature of 40°C.
[0070] The second coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 5% and a temperature of 20°C;
[0071] The thickness of the first coating layer is 2.0 μm, and the thickness of the third coating layer is 1.0 μm.
[0072] (3) Applying water-based PVDF slurry on the first coating to obtain a second coating, the thickness of the second coating is 1.0 μm, drying at 60° C. and rolling up to obtain the asymmetric structure coated diaphragm.
[0073] Among them, the SEM image of the second coating surface is as follows Figure 2 As shown, the SEM image of the third coating surface is as follows Figure 3 As shown, from Figure 2 and Figure 3 It can be seen that the second coating is a mixed coating of high temperature resistant polyamide and oily PVDF, and the microscopic morphology shows a small hole morphology. Figure 3 The third coating layer in the process is a roller-coated water-based PVDF layer.
[0074] Example 2
[0075] (1) dissolving meta-aramid polymer solution (weight average molecular weight of 150,000) in N,N-dimethylformamide, and adding pore former PVP K30 to obtain casting solution A; the mass fraction of meta-aramid in the casting solution A is 10 wt%, the slurry viscosity of the casting solution A is 3150 mpas; the mass content of the pore former in the casting solution A is 10%;
[0076] The meta-aramid polymer solution (weight average molecular weight of 150,000) and oily PVDF (weight average molecular weight of 400,000) are mixed in N,N-dimethylformamide at a certain solid content, and the pore-forming agent PVP K30 is added, and mechanically stirred for 1.0 h at 40°C. After the solution is completely dissolved, a casting solution B is obtained; in the casting solution B, the mass ratio of meta-aramid to PVDF is 1:1, and the slurry viscosity of the casting solution B is 500 mpas; the mass content of the pore-forming agent in the casting solution B is 10%;
[0077] (2) The casting liquid A and the casting liquid B are simultaneously coated on both sides of the base film through a micro-concave roller to form a first coating layer and a third coating layer respectively, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 50°C for 50 seconds for rinsing, and then roll up after drying;
[0078] The first coagulation bath is an aqueous solution of N,N-dimethylformamide with a mass concentration of 30% and a temperature of 30°C.
[0079] The second coagulation bath is an aqueous solution of N,N-dimethylformamide with a mass concentration of 5% and a temperature of 20°C;
[0080] The thickness of the first coating layer is 4.0 μm, and the thickness of the third coating layer is 4.0 μm.
[0081] (3) Applying water-based PVDF slurry on the first coating to obtain a second coating, the thickness of the second coating being 0.5 μm, drying at 40° C., and rolling up to obtain the asymmetric structure coated diaphragm.
[0082] Example 3
[0083] (1) dissolving meta-aramid polymer solution (weight average molecular weight of 250,000) in N-methylpyrrolidone, and adding pore former PVP K30 to obtain casting solution A; the mass content of meta-aramid in the casting solution A is 2%, the slurry viscosity of the casting solution A is 90 mpas; the mass content of the pore former in the casting solution A is 5%;
[0084] The meta-aramid polymer solution (weight average molecular weight of 250,000) and oily PVDF (weight average molecular weight of 800,000) were mixed in N-methylpyrrolidone at a certain solid content, and the pore-forming agent PVP K30 was added, and mechanically stirred for 0.5 h at 40°C. After the solution was completely dissolved, a casting solution B was obtained; in the casting solution B, the mass ratio of meta-aramid to PVDF was 1:10, and the slurry viscosity of the casting solution B was 63 mpas; the mass content of the pore-forming agent in the casting solution B was 5%;
[0085] (3) The casting liquid A and the casting liquid B are simultaneously coated on both sides of the base film through a micro-concave roller to form a first coating layer and a third coating layer respectively, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 80°C for 300 seconds for drying, and then roll up after drying;
[0086] The first coagulation bath is an aqueous solution of N-methylpyrrolidone with a mass concentration of 45% and a temperature of 60°C.
[0087] The second coagulation bath is an aqueous solution of N-methylpyrrolidone with a mass concentration of 15% and a temperature of 50°C;
[0088] The thickness of the first coating layer is 3.0 μm, and the thickness of the third coating layer is 1.0 μm.
[0089] (3) Applying water-based PVDF slurry on the first coating to obtain a second coating, the thickness of the second coating being 4 μm, drying at 40° C., and rolling up to obtain the asymmetric structure coated diaphragm.
[0090] Example 4
[0091] (1) A para-aramid polymer solution (weight average molecular weight of 80,000) was dissolved in N,N-dimethylacetamide, and a pore former PVP K30 was added to obtain a casting solution A; the mass content of para-aramid in the casting solution A was 2%, and the slurry viscosity of the casting solution A was 400 mpas; the mass content of the pore former in the casting solution A was 2%.
[0092] Para-aramid polymer solution (weight average molecular weight of 80,000) and oily PVDF (weight average molecular weight of 700,000) are mixed in N,N-dimethylacetamide at a certain solid content, pore former PVP K30 is added, mechanically stirred at 30°C for 1.0h, and casting solution B is obtained after complete dissolution; in the casting solution B, the mass ratio of para-aramid to PVDF is 1:4, and the slurry viscosity of the casting solution B is 240mpas; the mass content of the pore former in the casting solution B is 2%.
[0093] (2) The casting liquid A and the casting liquid B are simultaneously coated on both sides of the base film through a micro-concave roller to form a first coating layer and a third coating layer respectively, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40°C for 30 seconds after washing, and then rolled up after drying;
[0094] The first coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 40% and a temperature of 50°C.
[0095] The second coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 10% and a temperature of 30°C;
[0096] The thickness of the first coating layer is 1.0 μm, and the thickness of the third coating layer is 3.0 μm.
[0097] (3) Applying water-based PVDF slurry on the first coating to obtain a second coating, the thickness of the second coating is 2.0 μm, drying at 50° C. and rolling up to obtain the asymmetric structure coated diaphragm.
[0098] Example 5
[0099] (1) A para-aramid polymer solution (weight average molecular weight of 40,000) was dissolved in N,N-dimethylformamide, and a pore former PVP K30 was added to obtain a casting solution A; the mass content of para-aramid in the casting solution A was 10%, and the slurry viscosity of the casting solution A was 5000 mpas; the mass content of the pore former in the casting solution A was 4%.
[0100] Para-aramid polymer solution (weight average molecular weight of 40,000) and oily PVDF (weight average molecular weight of 550,000) are mixed in N,N-dimethylformamide at a certain solid content, pore former PVP K30 is added, mechanically stirred at 30°C for 1.0h, and casting solution B is obtained after complete dissolution; in the casting solution B, the mass ratio of para-aramid to PVDF is 1:6, and the slurry viscosity of the casting solution B is 8900mpas; the mass content of the pore former in the casting solution B is 4%.
[0101] (2) The casting liquid A and the casting liquid B are simultaneously coated on both sides of the base film through a micro-concave roller to form a first coating layer and a third coating layer respectively, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40°C for 30 seconds after washing, and then rolled up after drying;
[0102] The first coagulation bath is an aqueous solution of N,N-dimethylformamide with a mass concentration of 45% and a temperature of 45°C.
[0103] The second coagulation bath is an aqueous solution of N,N-dimethylformamide with a mass concentration of 10% and a temperature of 20°C;
[0104] The thickness of the first coating layer is 2.0 μm, and the thickness of the third coating layer is 2.0 μm.
[0105] (3) Applying water-based PVDF slurry on the first coating to obtain a second coating, the thickness of the second coating is 1.0 μm, drying at 50° C. and rolling up to obtain the asymmetric structure coated diaphragm.
[0106] Example 6
[0107] (1) A polyamide-imide polymer solution (weight average molecular weight of 100,000) was dissolved in N,N-dimethylacetamide, and a pore former PVP K90 was added to obtain a casting solution A; the mass content of polyamide-imide in the casting solution A was 10%, and the slurry viscosity of the casting solution A was 2100 mpas; the mass content of the pore former in the casting solution A was 1%.
[0108] A polyamide-imide polymer solution (weight average molecular weight of 100,000) and an oily PVDF (weight average molecular weight of 500,000) are mixed in N,N-dimethylacetamide at a certain solid content, a pore former PVP K90 is added, and mechanical stirring is performed at 40°C for 1.0h. After complete dissolution, a casting solution B is obtained; in the casting solution B, the mass ratio of polyamide-imide to PVDF is 1:2, and the slurry viscosity of the casting solution B is 150mpas; and the mass content of the pore former in the casting solution B is 1%.
[0109] (2) The casting liquid A and the casting liquid B are simultaneously coated on both sides of the base film through a micro-concave roller to form a first coating layer and a third coating layer respectively, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40°C for 30 seconds after washing, and then rolled up after drying;
[0110] The first coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 35% and a temperature of 50°C.
[0111] The second coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 5% and a temperature of 30°C;
[0112] The thickness of the first coating layer is 2.0 μm, and the thickness of the third coating layer is 3.0 μm.
[0113] (3) Applying water-based PVDF slurry on the first coating to obtain a second coating, the thickness of the second coating is 1.0 μm, drying at 50° C. and rolling up to obtain the asymmetric structure coated diaphragm.
[0114] Example 7
[0115] (1) A polyamide-imide polymer solution (weight average molecular weight of 300,000) was dissolved in N,N-dimethylformamide, and a pore former PVP K90 was added to obtain a casting solution A; the mass content of polyamide-imide in the casting solution A was 2%, and the slurry viscosity of the casting solution A was 120 mpas; the mass content of the pore former in the casting solution A was 3%.
[0116] A polyamide-imide polymer solution (weight average molecular weight of 300,000) and an oily PVDF (weight average molecular weight of 800,000) are mixed in N,N-dimethylformamide at a certain solid content, a pore former PVP K90 is added, and mechanical stirring is performed at 40°C for 1.0h. After complete dissolution, a casting liquid B is obtained; in the casting liquid B, the mass ratio of polyamide-imide to PVDF is 1:2, and the slurry viscosity of the casting liquid B is 45mpas; and the mass content of the pore former in the casting liquid B is 3%.
[0117] (2) The casting liquid A and the casting liquid B are simultaneously coated on both sides of the base film through a micro-concave roller to form a first coating layer and a third coating layer respectively, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40°C for 100 seconds for drying, and then roll up after drying;
[0118] The first coagulation bath is an aqueous solution of N,N-dimethylformamide with a mass concentration of 45% and a temperature of 40°C.
[0119] The second coagulation bath is an aqueous solution of N,N-dimethylformamide with a mass concentration of 10% and a temperature of 25°C;
[0120] The thickness of the first coating layer is 1.0 μm, and the thickness of the third coating layer is 2.0 μm.
[0121] (3) Applying water-based PVDF slurry on the first coating to obtain a second coating, the thickness of the second coating is 1.0 μm, drying at 40° C. and rolling up to obtain the asymmetric structure coated diaphragm.
[0122] Example 8
[0123] (1) A heterocyclic aramid polymer solution (the heterocyclic aramid is aromatic III with a weight average molecular weight of 200,000) is dissolved in N,N-dimethylformamide, and a pore former PVP K30 is added to obtain a casting solution A; the mass content of the heterocyclic aramid in the casting solution A is 10%, and the slurry viscosity of the casting solution A is 4500 mpas; the mass content of the pore former in the casting solution A is 2%.
[0124] A heterocyclic aramid polymer solution (the heterocyclic aramid is aromatic III with a weight average molecular weight of 200,000) and an oily PVDF (weight average molecular weight of 600,000) are mixed in N,N-dimethylformamide at a certain solid content, a pore former PVP K30 is added, and mechanical stirring is performed at 40°C for 1.0h. After complete dissolution, a casting solution B is obtained; in the casting solution B, the mass ratio of heterocyclic aramid to PVDF is 1:6, and the slurry viscosity of the casting solution B is 350mpas; and the mass content of the pore former in the casting solution B is 2%.
[0125] (2) The casting liquid A and the casting liquid B are simultaneously coated on both sides of the base film through a micro-concave roller to form a first coating layer and a third coating layer respectively, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40°C for 100 seconds for drying, and then roll up after drying;
[0126] The first coagulation bath is an aqueous solution of N,N-dimethylformamide with a mass concentration of 45% and a temperature of 55°C.
[0127] The second coagulation bath is an aqueous solution of N,N-dimethylformamide with a mass concentration of 5% and a temperature of 25°C;
[0128] The thickness of the first coating layer is 2.0 μm, and the thickness of the third coating layer is 3.0 μm.
[0129] (3) Applying water-based PVDF slurry on the first coating to obtain a second coating, the thickness of the second coating is 1.0 μm, drying at 40° C. and rolling up to obtain the asymmetric structure coated diaphragm.
[0130] Example 9
[0131] (1) A heterocyclic aramid polymer solution (the heterocyclic aramid is aromatic III with a weight average molecular weight of 400,000) is dissolved in N,N-dimethylacetamide, and a pore former PVP K30 is added to obtain a casting solution A; the mass content of the heterocyclic aramid in the casting solution A is 2%, and the slurry viscosity of the casting solution A is 300 mpas; the mass content of the pore former in the casting solution A is 3%.
[0132] A heterocyclic aramid polymer solution (the heterocyclic aramid is aromatic III with a weight average molecular weight of 400,000) and an oily PVDF (weight average molecular weight of 800,000) are mixed in N,N-dimethylacetamide at a certain solid content, a pore-forming agent PVP K30 is added, and mechanical stirring is performed at 40° C. for 1.0 h. After complete dissolution, a casting solution B is obtained; in the casting solution B, the mass ratio of the heterocyclic aramid to the PVDF is 1:3, and the slurry viscosity of the casting solution B is 100 mpas; and the mass content of the pore-forming agent in the casting solution B is 3%.
[0133] (2) The casting liquid A and the casting liquid B are simultaneously coated on both sides of the base film through a micro-concave roller to form a first coating layer and a third coating layer respectively, and then enter the first coagulation bath and the second coagulation bath in sequence, and then enter the drying oven at 40°C for 100 seconds for drying, and then roll up after drying;
[0134] The first coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 45% and a temperature of 60°C.
[0135] The second coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 10% and a temperature of 30°C;
[0136] The thickness of the first coating layer is 2.0 μm, and the thickness of the third coating layer is 4.0 μm.
[0137] (3) Applying water-based PVDF slurry on the first coating to obtain a second coating, the thickness of the second coating being 3.0 μm. Drying at 40° C. and rolling up to obtain the asymmetric structure coated diaphragm.
[0138] Comparative Example 1
[0139] The diaphragm was prepared by the same method as in Example 1, except that only PVDF was contained in the casting solution B, and no high temperature resistant aromatic polyamide was added.
[0140] Comparative Example 2
[0141] The diaphragm was prepared by the same method as in Example 1, except that in Comparative Example 2, the meta-aramid polymer solution was replaced with meta-aramid of the same molecular weight.
[0142] Comparative Example 3
[0143] The same method as in Example 1 was used to prepare the diaphragm, except that only one coagulation bath treatment was performed. The conditions for the one-stage coagulation bath in Comparative Example 3 were as follows: the coagulation bath was an aqueous solution of N,N-dimethylacetamide with a mass concentration of 25% and a coagulation bath temperature of 30°C.
[0144] Comparative Example 4
[0145] The diaphragm was prepared by the same method as in Example 1, except that the temperature of the second coagulation bath was increased so that the temperature difference between the first coagulation bath and the second coagulation bath was less than 10° C. In Comparative Example 5, the temperature of the second coagulation bath was 35° C.
[0146] Comparative Example 5
[0147] The diaphragm was prepared by the same method as in Example 1, except that the coagulation bath conditions were changed so that the concentration difference between the first coagulation bath and the second coagulation bath was less than 20%. In this comparative example 5, the first coagulation bath was an aqueous solution of N,N-dimethylacetamide with a mass concentration of 30%, and the temperature of the first coagulation bath was 40°C;
[0148] The second coagulation bath is an aqueous solution of N,N-dimethylacetamide with a mass concentration of 25%. The temperature of the second coagulation bath is 15°C.
[0149] Comparative Example 6
[0150] The diaphragm was prepared by the same method as in Example 1, except that the concentration of the first-stage coagulation bath was increased. In Comparative Example 6, the first-stage coagulation bath was an aqueous solution of N,N-dimethylacetamide with a mass concentration of 60%.
[0151] Comparative Example 7
[0152] The diaphragm was prepared by the same method as in Example 1, except that the concentration of the second coagulation bath was increased. In Comparative Example 7, the second coagulation bath was an aqueous solution of N,N-dimethylacetamide with a mass concentration of 20%.
[0153] Comparative Example 8
[0154] The diaphragm was prepared by the same method as in Example 1, except that the raw material oily PVDF was replaced. In this comparative example 8, the weight average molecular weight of the raw material oily PVDF was 400,000 (the difference in weight average molecular weight between PVDF and high temperature resistant aromatic polyamide in this comparative example 8 was 100,000).
[0155] The performance of the diaphragms prepared in the above examples and comparative examples was tested, and the specific results are shown in Table 1 below.
[0156] The detection methods involved are:
[0157] The hot-pressing bonding force testing method comprises the following steps:
[0158] (1) Fold the basement membrane in half along the midline and place it between two sheets of silicone oil paper;
[0159] (2) Turn on the plastic sealing heat press (U-H6330T) and set the parameters: temperature to 120°C and speed to 2700 mm / min;
[0160] (3) Place the diaphragm sample into the laminator from one side, take it out from the other side, and lay it flat on the cutting pad;
[0161] (4) Use a 15 mm cutter to cut a coated diaphragm sample with a width of 15.0 mm and a length of >18 cm;
[0162] (5) Turn on the switch of the electronic tensile testing machine and test the peel strength of the sample. For specific operations, refer to the provisions of 6.5.6 in T / CPPIA10-2021.
[0163] The test method for film rupture temperature is as follows: in accordance with GB / T 36800.1, the sample size is 8.0×4.0 mm in length and width, and the specific test method is as follows:
[0164] 1) Cut the sample into strips with a size of 8 × 4 mm in length × width in the MD and TD directions respectively, and fix them in the fixture of the instrument;
[0165] 2) Select the thin film probe and quartz platform, place the sample on the sample platform, set the test parameters: preload force is 0.03N, high-purity nitrogen flow rate is 40mL / min, temperature rise range is 50-300℃, rate is 5℃ / min, and start measurement;
[0166] 3) Take the measured value as the test result.
[0167] Table 1 Diaphragm performance data
[0168]
[0169] From the above data, it can be seen that the diaphragms prepared by the preparation method of the present invention in Examples 1 to 9 can meet the different hot pressing bonding forces of the positive and negative electrodes, the air permeability value is ≤300s / 100cc, and the membrane rupture temperature is ≥250°C.
[0170] From the data comparison of Example 1 and Comparative Example 1, it can be seen that if the second coating only has PVDF, the adjustment of hot pressing bonding force cannot be achieved, so the battery process with different bonding force between positive and negative electrodes cannot be met, and the membrane rupture temperature is very low, which makes it difficult to meet the battery safety requirements.
[0171] From the data comparison of Example 1 and Comparative Example 2, it can be seen that after replacing the meta-aramid polymer liquid with aramid fiber, the hot pressing bonding strength of the diaphragm coating will be reduced, the air permeability value will be increased and the membrane rupture temperature will be reduced. This is because when the aramid fiber is redissolved, there will be a microcrystalline structure in which the fiber is not completely dissolved, which affects the diaphragm's properties such as bonding strength, air permeability and membrane rupture temperature.
[0172] From the data comparison of Example 1 and Comparative Example 3, it can be seen that when only one-stage coagulation bath is adopted, high-temperature resistant aromatic polyamide and PVDF are precipitated simultaneously, which is not conducive to the formation of PVDF on the surface of the diaphragm, resulting in a decrease in adhesion, and the diaphragm obtained by the one-stage coagulation bath has a lower porosity and poorer air permeability.
[0173] From the data comparison of Example 1 and Comparative Examples 4 and 5, it can be seen that reducing the concentration difference or temperature difference between the first-stage coagulation bath and the second-stage coagulation bath will reduce the hot pressing bonding strength to varying degrees. The effect of temperature on the hot pressing bonding strength of the diaphragm coating is more obvious than that of concentration. This indicates that the effect of temperature on the molding speed of high-temperature resistant polymers and PVDF is higher than that of concentration.
[0174] From the data comparison of Example 1 and Comparative Examples 6 and 7, it can be seen that if the concentration of the first coagulation bath or the second coagulation bath increases, it will affect the hot pressing adhesion performance of the second coating and the air permeability of the entire diaphragm. Because if the concentration of the coagulation bath is high, the pore size formed by the first coating is larger, and when coating water-based PVDF, a large amount of water-based PVDF will fall into the pores of the first coating, thereby affecting the adhesion performance of the second coating and the air permeability of the diaphragm.
[0175] From the data comparison between Example 1 and Comparative Example 8, it can be seen that the smaller the difference between the molecular weights of the high-temperature resistant aromatic polyamide and PVDF, the more it will affect the molding process of the high-temperature resistant aromatic polyamide and PVDF in the coagulation bath. The smaller the difference, the closer the molding speeds are, and PVDF and aramid will be molded on the coating surface at the same time, which is more conducive to the diaphragm having good bonding properties.
[0176] Application Example 1-9 and Comparative Application Example 1-8
[0177] The diaphragm obtained in the above example is assembled into a 4Ah 811 system ternary lithium battery using a lamination process.
[0178] The batteries assembled with the separators of the above Examples 1-9 and Comparative Examples 1-8 correspond to Application Examples 1-10 and Comparative Application Examples 1-6, respectively.
[0179] Application Comparative Example 9
[0180] The battery was assembled using the same method as in Application Example 1, except that the separator was replaced with a commercially available (1+2+7+2+1) μm PE / ceramic / PVDF coating membrane, where 2 is the ceramic coating thickness, 1 is the coating thickness of the water-based roller-coated PVDF, and 7 is the PE base membrane thickness.
[0181] The batteries of the above application examples and application comparison examples were subjected to performance tests, and the specific test results are shown in Table 2 below.
[0182] Table 2 Battery performance test results
[0183]
[0184] From the above table data, it can be seen that the diaphragm prepared by the preparation method of the present invention in the battery of application examples 1-9 has an improved capacity retention rate after 100 cycles compared with the PE / ceramic / PVDF coating film, all of which are above 90%, which can effectively improve the battery cycle life. In the Arc (accelerating calorimeter) test, the application comparison example 9 does not have a high-temperature resistant polyamide coating layer, and the measured Arc temperature is 686°C, while the application examples 1-8 with high-temperature resistant aromatic polyamide coatings have their Arc temperatures reduced to below 600°C, among which the high-temperature resistant aromatic polyamides in application examples 4-5 and application examples 8-9 respectively use para-aramid and aromatic III with better heat resistance, and the Arc temperature of the battery prepared by the diaphragm is also the lowest, which are 435, 415°C and 425, 420°C, respectively. It can be seen from this that the asymmetric structure coated diaphragm prepared by the preparation method of the present invention has good application performance in the battery.
[0185] From the data comparison between Application Example 1 and Application Comparative Example 1, it can be seen that: only PVDF is used in the second coating without high-temperature resistant polyamide, the adhesion of the second coating is very large, and the ARC temperature of the prepared diaphragm increases, and the safety is reduced.
[0186] From the data comparison between Application Example 1 and Application Comparative Example 2, it can be seen that after the aramid polymer solution is converted into aramid fiber, the DCR value increases. This is because the incompletely dissolved aramid microcrystalline structure increases the internal resistance of the battery, thereby affecting the cycle life, and its capacity retention rate is also reduced.
[0187] From the data comparison between Application Example 1 and Application Comparative Example 3, it can be seen that the DCR value of Application Comparative Example 3 is improved compared with Application Example 1. This is because the first-stage coagulation bath regulates the pore structure of the aromatic polyamide and PVDF coating during the molding process, with low porosity and high air permeability, and the pore structure is not uniform without the two-stage coagulation bath, which ultimately leads to a decrease in capacity retention. From the data comparison between Application Example 1 and Application Comparative Example 4 and Application Comparative Example 5, it can be seen that the concentration difference between the first-stage coagulation bath and the second-stage coagulation bath in Application Comparative Example 5 is less than 20%, and the temperature difference between the first-stage coagulation bath and the second-stage coagulation bath in Application Comparative Example 4 is less than 10°C. The difference in concentration and temperature of the two-stage coagulation bath is too small, which makes the difference in the order of high-temperature resistant aromatic polyamide and PVDF in the molding process small, and PVDF and aromatic polyamide are distributed more evenly, which reduces the bonding force between the coating and the pole piece, thereby affecting the ionic conductivity and DCR value, and affecting the capacity retention rate. However, from the data, the influence of temperature is greater than that of concentration, which is consistent with the performance data such as the hot pressing bonding force of the diaphragm in Table 1.
[0188] From the data comparison of Application Example 1 and Application Comparative Examples 6 and 7, it can be seen that after the concentration of the primary coagulation bath or the secondary coagulation bath is increased, the adhesion of the diaphragm is reduced, resulting in an increase in the battery DCR.
[0189] From the data comparison between Application Example 1 and Application Comparative Example 8, it can be seen that the difference in molecular weight between aromatic polyamide and PVDF has a smaller impact on the difference in safety performance, but a greater impact on battery performance. This is mainly because the large difference in molecular weight is more conducive to the sequence of aromatic polyamide and PVDF in the molding process, so that more PVDF is molded on the coating surface, which is conducive to increasing the amount of effective PVDF, thereby improving the adhesion of the coating. Therefore, the capacity retention rate of Application Comparative Example 6 is reduced.
[0190] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0191] For those skilled in the art, several modifications and improvements may be made without departing from the concept of the present invention, all of which belong to the protection scope of the present invention. The protection scope of the present invention shall be based on the attached claims.
Claims
1. A method for preparing an asymmetric structure coated diaphragm, characterized in that: The asymmetric structure coated diaphragm comprises a base film, two sides of the base film are respectively provided with a first coating layer and a third coating layer, and the first coating layer is provided with a second coating layer; The first coating is high temperature resistant aromatic polyamide; the third coating includes high temperature resistant aromatic polyamide and oily PVDF; the second coating is water-based PVDF; The preparation method is: S1, dispersing the high temperature resistant aromatic polyamide polymer solution in a polar solvent to obtain a casting solution A; Mixing a high temperature resistant aromatic polyamide polymer solution and an oily PVDF in a polar solvent, and mixing them evenly to obtain a casting solution B; S2, coating the casting liquid A and the casting liquid B on both sides of the base film to form a first coating layer and a third coating layer, and then performing a two-stage coagulation bath treatment, and finally washing and drying; S3, coating the first coating with water-based PVDF slurry to obtain a second coating, drying and rolling up to obtain the asymmetric structure coated diaphragm; The high temperature resistant aromatic polyamide is meta-aramid, para-aramid, heterocyclic aramid or polyamide-imide; the weight average molecular weight difference between the oily PVDF and the meta-aramid is not less than 250,000; the weight average molecular weight difference between the oily PVDF and the para-aramid is not less than 400,000; the weight average molecular weight difference between the oily PVDF and the heterocyclic aramid is not less than 250,000; the weight average molecular weight difference between the oily PVDF and the polyamide-imide is not less than 350,000; The weight average molecular weight of the meta-aramid is 150,000-250,000; the weight average molecular weight of the para-aramid is 40,000-80,000; the weight average molecular weight of the heterocyclic aramid is 200,000-400,000; the weight average molecular weight of the polyamide-imide is 100,000-300,000; the weight average molecular weight of the oily PVDF is 400,000-800,000; The coagulation bath is a mixed solution of a polar solvent and water, the mass concentration of the polar solvent in the first coagulation bath is 30%-45%, and the temperature of the first coagulation bath is 30-60°C; the mass concentration of the polar solvent in the second coagulation bath is 5%-15%, and the temperature of the second coagulation bath is 20-50°C; The concentration difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥20%, and the temperature difference between the first-stage coagulation bath and the second-stage coagulation bath is ≥10°C.
2. The method for preparing an asymmetric structure coated diaphragm according to claim 1, characterized in that: The first coating has a thickness of 0.5-4.0 μm, the third coating has a thickness of 0.5-4.0 μm, and the second coating has a thickness of 0.5-4.0 μm; In the third coating, the mass ratio of high temperature resistant aromatic polyamide to oily PVDF is 1:(1-10); the hot pressing bonding force of the third coating is 1-30 N / m 2 The hot pressing bonding force of the second coating is 2-12 N / m 2 .
3. The method for preparing an asymmetric structure coated diaphragm according to claim 1, characterized in that: The air permeability of the asymmetric structure coated diaphragm is ≤300s / 100cc, and the membrane breaking temperature is ≥250°C.
4. The method for preparing an asymmetric structure coated diaphragm according to claim 1, characterized in that: A pore-forming agent is added or not added to the casting liquid A and the casting liquid B, the mass content of the pore-forming agent in the casting liquid A is 0%-10%, and the mass content of the pore-forming agent in the casting liquid B is 0%-10%; The porosity of the first coating layer is 30-70%, and the porosity of the third coating layer is 30-70%.
5. A battery, characterized in that: The battery contains an asymmetric structure coated diaphragm prepared according to the preparation method of any one of claims 1-4.
Citation Information
Patent Citations
Aramid coated lithium ion battery diaphragm and preparation method thereof
CN104993089A
Composite coating lithium-ion battery separator and preparation method thereof
CN105552284A
Preparation method of high-heat-resistance vinylidene fluoride polymer mixed coating diaphragm
CN110635090A
KR20240108973A